2000
DOI: 10.1182/blood.v96.5.1685
|View full text |Cite
|
Sign up to set email alerts
|

Effect of active prenatal management on pregnancy outcome in sickle cell disease in an African setting

Abstract: Sickle cell disease (SCD) is associated with an increased risk of medical complications during pregnancy. In sub-Saharan Africa, fetal and maternal mortality rates are particularly high. This study evaluated the effect of an active prenatal management program on pregnancy outcome in patients with SCD in an African setting. Pregnant women with SCD attending the National Teaching Hospital in Cotonou (The Republic of Benin, West Africa) were recruited before the 28th week of gestation. Management was based on pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 17 publications
1
23
0
1
Order By: Relevance
“…For example, in Benin where neonatal screening and comprehensive health care management were practiced, the under-five mortality rate of SCD was 15.5 per 10 000, which is ten times lower than the overall under-five mortality rate. 20,21 These results are comparable with those in high-income countries, demonstrating the advantages of newborn screening and close follow-up of children in a comprehensive care approach. 22 Despite the overwhelming evidence of the efficacy of newborn screening for SCD, no country in SSA with 75% of the world's disease burden has a universal newborn screening program in place.…”
Section: Newborn/neonatal Screening and Comprehensive Caresupporting
confidence: 61%
See 1 more Smart Citation
“…For example, in Benin where neonatal screening and comprehensive health care management were practiced, the under-five mortality rate of SCD was 15.5 per 10 000, which is ten times lower than the overall under-five mortality rate. 20,21 These results are comparable with those in high-income countries, demonstrating the advantages of newborn screening and close follow-up of children in a comprehensive care approach. 22 Despite the overwhelming evidence of the efficacy of newborn screening for SCD, no country in SSA with 75% of the world's disease burden has a universal newborn screening program in place.…”
Section: Newborn/neonatal Screening and Comprehensive Caresupporting
confidence: 61%
“…25 Educational programs regarding the timely recognition of signs of infection and prompt clinical care are best accomplished in the setting of neonatal screening programs. 21,25 The HbS gene mutation is included in a number of genetic alterations that have been shown to have a similar distribution to that of endemic malaria. Geographically, an association exists between the areas of the highest HbS allele frequencies and high malaria endemicity globally, as has been elegantly shown in sub-Saharan Africa, where the carrier state (sickle cell trait) is extremely common.…”
Section: -5 Years Of a Child's Life Thus Instituting Such Servicesmentioning
confidence: 99%
“…In addition, the odds of fetal death, preterm birth, low birthweight, and cesarean delivery were higher for females with SCD compared with those with no reported hemoglobinopathies after adjusting for maternal age, education, parity, plurality, insurance status at delivery, prenatal care utilization, smoking, and infant sex. [6][7][8][9] The maternal mortality rate was 1.6 per 1000 deliveries in patients, compared to 0.1 per 1000 in women without SCD. Pregnant women with SCD had a higher risk for preeclampsia, eclampsia, venous thromboembolism, cardiomyopathy, intrauterine fetal demise, and intrauterine growth restriction.…”
mentioning
confidence: 95%
“…and treatment for individuals with SCD, coupled with advancements in neonatal care, have contributed to a decline in morbidity and mortality both for mother and fetus; however, the physiologic changes in pregnancy still carry important clinical risks for some patients with SCD. 8,9 Previous studies have reported that females with SCD had a higher prevalence of preeclampsia, lung disease, and heart disease during the antenatal, intrapartum, or postpartum periods compared with women without hemoglobinopathies. In addition, the odds of fetal death, preterm birth, low birthweight, and cesarean delivery were higher for females with SCD compared with those with no reported hemoglobinopathies after adjusting for maternal age, education, parity, plurality, insurance status at delivery, prenatal care utilization, smoking, and infant sex.…”
mentioning
confidence: 99%
See 1 more Smart Citation